2005
DOI: 10.1021/ja044325h
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Scanning:  Total Synthesis of Demethylasterriquinone B1 and Derivatives for Identification of Sites of Interaction with and Isolation of Its Receptor(s)

Abstract: The principle of methyl scanning is proposed for determination of the sites of interaction between biologically active small molecules and their macromolecular target(s). It involves the systematic preparation of a family of methylated derivatives of a compound and their biological testing. As a functional assay, the method can identify the regions of a molecule that are important (and unimportant) for biological activity against even unknown targets, and thus provides an excellent complement to structural bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 37 publications
1
56
1
Order By: Relevance
“…Our finding that the 7-prenyl-indole ring is the active substructure of DAQ-B1 confirms our previous conclusion from a methylation-scanning study of the parental compound. In that study, we found that methyl substitution on the 7-prenyl-indole ring was not tolerated; however, methyl substitution on the 2 isoprenylindole ring did not alter activity (Pirrung et al, 2005). We concluded that the 7-prenyl-indole, but not the 2-isoprenylindole, probably makes close contacts with the insulin receptor kinase domain.…”
Section: Discussionmentioning
confidence: 86%
“…Our finding that the 7-prenyl-indole ring is the active substructure of DAQ-B1 confirms our previous conclusion from a methylation-scanning study of the parental compound. In that study, we found that methyl substitution on the 7-prenyl-indole ring was not tolerated; however, methyl substitution on the 2 isoprenylindole ring did not alter activity (Pirrung et al, 2005). We concluded that the 7-prenyl-indole, but not the 2-isoprenylindole, probably makes close contacts with the insulin receptor kinase domain.…”
Section: Discussionmentioning
confidence: 86%
“…1B). Details of the synthetic route have been published previously (Pirrung et al, 2005b). Aliphatic, aromatic, and halogen substitutions were included at different positions on the indole rings and the hydroxyl of the quinone ring, generating 14 possible substitution positions ( Fig.…”
Section: Screening Combinatorial Libraries For Activation Ofmentioning
confidence: 99%
“…More recently, Pirrung reported the synthesis of bis(indolyl)-1,4-benzoquinone under relatively intense reaction conditions: using Zn(OTf) 2 (1 equiv.) as catalyst and THF as solvent, refluxing for 26 h under nitrogen followed by oxidation with DDQ, [12] or by coupling with mercury reagents catalyzed by Pd II /Cu-(OAc) 2 . [13] We report herein a highly efficient "on water"-promoted direct coupling of indole compounds with 1,4-benzoquinones (Scheme 1) without the use of any catalyst, additive, or organic solvent.…”
mentioning
confidence: 99%